Pengelolaan Program Pembinaan Kader Perempuan di Lingkungan Kohati (Korps HmI-Wati) Cabang Bandung - Iqhlima Yustpika Putri; Nan Rahminawati; Asep Dudi Suhardini (UNISBA Press, 2024)
Abstract. The HmI-Wati Corps (Kohati) is part of a special body within HmI that focuses on fostering women related to issues related to women. Kohati was inaugurated during the congress in Solo on the fourth decree on September 17, 1966 with Kohati's basic guideline